Strength and durability characteristics of polymer-modified carbon fiber concrete - Pacheco-Torgal, F. (2010)
Carbon-fiber concrete (CFC) materials are gaining momentum due to the reduction of carbon fiber cost and also to the sensing performance of carbon fiber reinforced concrete based structures. For carbon fiber concrete electrical resistance increases with tensile stress and decreases upon compression. Therefore CFC can act as self-monitoring strain sensor. Nevertheless, fiber incorporation is responsible for a loss in concrete workability, and also for a slightly compression strength reduction related to an increase in air content. Although shortterm mechanical properties of these materials are well documented, durability issues still need further investigations efforts. This paper reports some results on the strength and durability characteristics of several concrete mixtures made with different polymer and carbon fiber addition percentage. Results show that carbon fiber addition decreases strength and increases water penetration under pressure and also increases chloride diffusion, while the polymer addition reduces water penetration and concrete permeability.